Differences in Physicians' and Nurses' Recent Suicide Attempts: An Exploratory Study. Issue 2 (2nd April 2016) - Braquehais, María Dolores; Eiroa-Orosa, Francisco José; Holmes, Kristin M.; Lusilla, Pilar; Bravo, Maria; Mozo, Xulián; Mezzatesta, Marcela; Casanovas, Marta; Pujol, Tània; Sher, Leo
Abstract : The aim of this study was to examine the characteristics of physicians' and nurses' suicide attempts (SA). A retrospective review of 493 medical records of physicians and nurses admitted to an inpatient unit for health professionals; 36 patients had a recent SA. Depression, cluster B and C personality disorders, and a history of previous SA were more prevalent in patients with a recent SA compared to those without it. Both professional groups preferred drug overdose as a suicide method. Physicians made more lethal attempts and had a history of more previous stressors than nurses. Depression, cluster B and C personality disorders, and previous SA should be appropriately screened and treated in order to prevent SA amongst physicians and nurses.